2018
DOI: 10.1016/j.nicl.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural connectivity of the amygdala underpins locus of control in mild cognitive impairment

Abstract: Locus of control (LOC) is an important personality trait. LOC over cognitive competency reflects an individual's perceived control of desired cognitive outcomes, which is critical for maintaining successful cognitive aging. It is important to understand the neural substrates of LOC over cognitive competency in older adults, especially for individuals at high risk of dementia. Here, we characterized a cohesive functional and structural connectivity profile underlying LOC among 55 older adults with amnestic mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Almeida and colleagues reported reduced amygdala-orbitofrontal cortex (OFC) FC during the processing of happy and sad faces in medicated patients with MDD (20). Using fMRI and diffusion tensor imaging data from 55 older adults with amnestic MCI, another study found that both functional and structural connectivities between the medial prefrontal cortex and amygdala were significantly correlated with external LOC (21). Using the coherence regional homogeneity method, we previously reported that D-MCI patients had abnormal temporal homogeneity compared with patients with no depression with MCI (nD-MCI) in the mPFC, post-central gyrus, and thalamus (22).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almeida and colleagues reported reduced amygdala-orbitofrontal cortex (OFC) FC during the processing of happy and sad faces in medicated patients with MDD (20). Using fMRI and diffusion tensor imaging data from 55 older adults with amnestic MCI, another study found that both functional and structural connectivities between the medial prefrontal cortex and amygdala were significantly correlated with external LOC (21). Using the coherence regional homogeneity method, we previously reported that D-MCI patients had abnormal temporal homogeneity compared with patients with no depression with MCI (nD-MCI) in the mPFC, post-central gyrus, and thalamus (22).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of the amygdala-mPFC circuit have been widely reported in patients with depression (15)(16)(17)(18)(19)(20)(21). Using data from 100 fMRI experiments, one meta-analysis showed that hyperactivation of the mPFC is associated with diminished right amygdala activity during the regulation of negative emotions (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and premorbid personality traits (such as internal or externa locus of control) in addition to the severity of AD pathology assessed with CSF. 34 , 87 , 88 …”
Section: Resultsmentioning
confidence: 99%